Preoperative Imaging Risk Findings for Postoperative New Stroke in Patients With Acute Type A Aortic Dissection - Zhao, Hongliang; Guo, Fan; Xu, Jingji; Zhu, Yuanqiang; Wen, Didi; Duan, Weixun; Zheng, Minwen (Frontiers in Cardiovascular Medicine, 2020)
Background: Stroke is a common postoperative complication in patients with acute type A aortic dissection (ATAAD). We aimed to explore the preoperative imaging risk findings for postoperative new stroke in patients with ATAAD. Methods: From January 2015 to December 2018, 174 patients with ATAAD who underwent preoperative aortic computed tomography angiography (CTA) and cerebral diffusion-weighted imaging (DWI) as well as postoperative brain CT were included, and divided into DWI (+) and DWI (-) groups. Pre- and intraoperative variables were collected, and logistic regression analysis was used to determine the independent risk predictors of postoperative new stroke. Results: The incidence of postoperative new stroke was 18.4% (32/174) in patients with ATAAD. Postoperative stroke was detected in 13 (31.0%) patients in the DWI (+) group and in 19 (14.4%) patients in the DWI (-) group with significant difference (P = 0.016). In the DWI (+) group, the lesions of the cerebral infarction located in the unilateral cerebral hemisphere and distributed more than three lobes (P = 0.007) were an independent risk factor for postoperative new stroke. Hypotension (P = 0.002), retrograde ascending aorta dissection with thrombosis of the false lumen (P = 0.010), aortic arch entry (P = 0.035), and coronary artery involvement (P = 0.001) were independent risk factors for postoperative stroke in the DWI (-) cohort. Conclusions: Patients with ATAAD with cerebral infarction are more likely to develop postoperative new stroke; thus, a preoperative DWI examination may be necessary. DWI lesions distributed more than 3 lobes in the unilateral hemisphere suggest a high possibility of postoperative stroke. For patients with ATAAD with normal brain, particular attention should be given to the CTA findings of false lumen thrombosis, aortic arch entry, and coronary artery involvement to avoid postoperative stroke.